Butch Cassidy and the Sundance Kid [videorecording (DVD)] - Hill, George Roy, 1921-2002; Newman, Paul, 1925-2008; Redford, Robert; Ross, Katharine, 1940- (20th Century Fox Home Entertainment, 2006)
The Sundance Kid is the frontier's fastest gun. His partner, Butch Cassidy is always dreaming up new ways to get rich fast. If only they could blow open a baggage car without also blowing up the money-filled safe inside. So Butch and Sundance pack their guns, put on new duds, and, with Sundance's girlfriend, head down to Bolivia.